The Role of Mitochondria in AMD: Current Knowledge and Future Applications - Riazi-Esfahani, Mohammad (J Ophthalmic Vis Res, 2017)
Mitochondria are organelles which comprise the main respiratory machinery in the eukaryotic cells. In addition to their crucial role in energy production, they have profound effects on apoptosis and retrograde signaling to nucleus. Mitochondria have their own DNA, which codes for different proteins mostly involved in oxidative phosphorylation. Significant changes in the mitochondria of retinal pigment epithelium have been reported in age-related macular degeneration (AMD), which is correlated with the severity of the disease. Cybrid cell lines that have identical nuclei but mitochondria from different individuals can provide a unique means for studying the relationship between mitochondria and AMD. Different approaches for protection of mitochondria have been introduced which can be considered as potential future treatments for AMD and other age- related disorders.